Coding And Artificial Intelligence Learning in Improving the Digital Skills of Grade 5 Elementary School Students (Case study at SDN 2 Cikumpay, Purwakarta Regency) - Ina Nurmuminah; Tatang Permana; Acep Supriatna; Waska Warta (Global Education Journal, 2025)
his study aims to describe and analyze the effectiveness of coding and Artificial Intelligence learning in improving the digital skills of grade 5 students at SDN 2 Cikumpay, Purwakarta Regency. This research is motivated by the competency demands of the Industry 4.0 and 5.0 era, as well as the initial findings that students' digital skills are still diverse and not optimal. The method used in this study is qualitative with the type of case study. Data collection techniques include participatory observation, in-depth interviews, and documentation studies, which are then analyzed using the PDCA (Plan, Do, Check, Act) quality management cycle. The results of the study show that: (1) At the Plan stage, schools procure infrastructure and prepare unplugged and plugged-based adaptive teaching modules; (2) At the Do level, learning is carried out interactively (student-centered) using the Scratch and Google Gemini  platforms to train digital logic and ethics; (3) At the Check stage, it was recorded that most of the 5th grade students were proficient in operating software, understanding algorithm logic, and having digital security awareness; and (4) At the Act stage, follow-up will be carried out in the form of organizing a "Digital Work Exhibition" and the appointment of students as School Digital Ambassadors. This study concludes that the integration of KKA in a structured and effective manner can improve students' digital skills, especially in the computational thinking skills of grade 5 elementary school students.